Bound together : leather, sex, archives, and contemporary art - Campbell, Andy, 1982- (Rethinking art's histories., 2020)
This book examines US gay and lesbian leather archives alongside contemporary artistic practices that reframe and renegotiate historical source material, creating a queer politics of the present.